SUBSIDI LPG 3 KG DALAM PERSPEKTIF SOSIOLOGI KEBIJAKAN: DAMPAKNYA TERHADAP KESEJAHTERAAN DAN LINGKUNGAN DI JAWA BARAT - Riki Satia Muharam; Budiman Rusli; Nina Karlina; Candradewini Candradewini (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study aims to analyze the 3 Kg LPG subsidy policy in West Java Province from the perspective of policy sociology, focusing on its impact on community welfare and the accompanying social dynamics. The 3 Kg LPG subsidy was designed to ease the energy expenditure burden of poor households and improve access to affordable clean energy. However, its implementation faces several challenges, including mistargeting, unequal distribution, social dependency on subsidies, and limited public participation in the policy-making process. Using a qualitative descriptive approach and thematic analysis of interview data, observations, and policy documents, the study finds that the 3 Kg LPG subsidy policy reflects unequal power relations at the local level and results in structural injustice in energy distribution. Therefore, policy reform is required through improvements in data-based distribution systems, increased public participation, and a transition toward inclusive and equitable renewable energy. These findings provide important insights for the formulation of fairer and more sustainable energy policies in Indonesia.